Artificial intelligence and public health context: what we should know? - Faerozh Madli; Yuzainy Janin; Shaierah Gulabdin; Suddin Lada; Wong Sing Yun; Azaze-Azizi Abdul Adis; Adi Jafar (Penerbit Akademia Baru, 2024)
The rapid technological advancement nowadays has a wide-ranging impact on almost all industries. Artificial Intelligence (AI) is one of the technologies that has received much attention and has been used widely, including in the public health sector. In this light, medical practitioners and the public are anticipating the changes brought by AI technology in the public health sector. This study is focused on thoroughly discussing the relationship of AI in the context of public health. The discussion shows that AI is giving a lot of positive potential to the public health sector. However, despite the abundant potential and promise, AI is also not running away from today's challenges. The overall discussion of this study will provide a clear picture on the link between AI, public health link and related parties, including official medical-related agencies. In other words, this paper summarises the relationship between AI and public health, specifically the challenges and potential changes AI will bring forward.